2021
DOI: 10.1155/2021/6686857
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Advanced Platelet-Rich Fibrin in comparison with Leukocyte-Platelet-Rich Fibrin on Outcome after Dentoalveolar Surgery

Abstract: Background and Purpose. Some physiological changes may occur following tooth extraction, and symptoms during the postextraction period may affect the patient’s quality of life. Many techniques have been developed to improve postextraction pain and soft tissue healing. Accordingly, this study will compare the postextraction pain and early soft tissue healing characteristics of extraction sites treated with leukocyte-platelet-rich fibrin (L-PRF) and advanced platelet-rich fibrin (A-PRF). The aim is to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…When compared to PRF, A-PRF improves periodontal weakened sites by regenerating tissues by increasing parameters like probing depth, lowering relative attachment loss, and increasing bone height, which is similar to infrabony pocket treatment [8]. A-PRF improves soft tissue recovery at extraction sites and reduces postoperative discomfort and the requirement for analgesics [7]. The increase of VEGF expression by A-PRF had a beneficial effect on the angiogenesis of the gingiva.…”
Section: Clinical Applicationsmentioning
confidence: 89%
See 1 more Smart Citation
“…When compared to PRF, A-PRF improves periodontal weakened sites by regenerating tissues by increasing parameters like probing depth, lowering relative attachment loss, and increasing bone height, which is similar to infrabony pocket treatment [8]. A-PRF improves soft tissue recovery at extraction sites and reduces postoperative discomfort and the requirement for analgesics [7]. The increase of VEGF expression by A-PRF had a beneficial effect on the angiogenesis of the gingiva.…”
Section: Clinical Applicationsmentioning
confidence: 89%
“…The tubes of the A-PRF group underwent 14-minute centrifugation at 1500 rpm. The final tube product was composed of the following three layers: the very first layer that is of acellular plasma, A-PRF clot that lies in the center, and RBCs that last at the bottom [7].…”
Section: Preparation Of A-prfmentioning
confidence: 99%
“…However, no difference in the postoperative swelling was observed between L-PRF and A-PRF (15). Contradictory to this, in the study by Makki et al, it was observed that the A-PRF group responded better than the L-PRF group in terms of postoperative pain score and number of painkillers (16). This can be attributed to the disadvantages of PRF that they're not useful for large wounds as the PRF quantity reduces if the autologous blood sample quantity is low (17,18).…”
Section: Discussionmentioning
confidence: 93%
“…Following the filling of the post-extraction alveolus with the PRF clot, neovascularization is established, and an epithelial covering develops. Although there is potential for infection and inflammation of the extraction socket, rapid wound healing occurs without pain or other complications [ 54 , 55 , 56 , 65 , 66 ]. The next generation of PRF, advanced platelet-rich fibrin (A-PRF), is obtained in low-speed centrifugation, and is considered a new autologous material that has numerous benefits in implant dentistry [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…A-PRF helped increase bone density, epithelial healing, and control postoperative pain and swelling after tooth extraction [ 46 ]. In the study carried out by Makki et al comparing the use of A-PRF with L-PRF in post-extraction alveoli, it was shown that the use of A-PRF significantly reduced postoperative pain and improved early soft tissue healing [ 66 ]. The same results were obtained in other studies in the literature [ 67 , 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%